Assessment of selected soil chemical properties at different depths and altitudes for groundnut (Arachis hypogaea L.) production in Hakim Gara shrub land of Harari Region of eastern Ethiopia: ASSESSMENT OF SOIL CHEMICAL PROPERTIES FOR GROUNDNUT IN HARARI REGION OF ETHIOPIA - VIJAY SINGH; TADELE GENETI (Journal of Oilseeds Research, 2020)
Ethiopia has a huge potential for growing and exporting various low land oilseed crops like niger (noug), linseed, mustard, sesame, groundnut and safflower. Currently the present achievements are very low because of least share of land and input to these crops resulting in low production and productivity. The present study was conducted to assess the suitability of soil chemical properties at different depths and altitudes for production of low land oil seed crop groundnut (Arachis hypogaea L.) which is the major crop in HakimGara shrub land of Harari Region of eastern Ethiopia. Soil samples were collected along with altitudinal gradients of the land features between 2001 and 2113 meters above sea level at 0-20 cm and 20-40 cmdepths. There were decreasing trend recorded in soil organic matter, soil organic carbon, cation exchange capacity and total nitrogen i.e. 5.52 to 12.24, 3.20 to 7.10 %, 35.2 to 50.6 cmol(+)/kg and 0.1 to 0.8 %, respectively. However, slight increase in pH was recorded with increase in soil depth except for soil of upper altitude. Percent total nitrogen, cation exchange capacity and altitude were positively correlated with soil organic carbon. While pH and depth were negatively correlated with soil organic carbon. Thus, soil chemical properties are the most important management interventions that are to be addressed to increase the groundnut production capacity in Hakim Gara shrub land. Therefore, stakeholders should focus on management activities that improve soil chemical properties to boost groundnut production capacity of the soil in this region of Ethiopia.